Challenges and opportunities for improving food quality and nutrition through plant biotechnology. (April 2017) - Francis, David; Finer, John J; Grotewold, Erich
Graphical abstract: Highlights: Plant biotechnology has been around since the beginning of humankind. Genome editing technologies complement and enhance breeding and selection. GMOs are just one aspect of plant biotechnology. Abstract : Plant biotechnology has been around since the advent of humankind, resulting in tremendous improvements in plant cultivation through crop domestication, breeding and selection. The emergence of transgenic approaches involving the introduction of defined DNA sequences into plants by humans has rapidly changed the surface of our planet by further expanding the gene pool used by plant breeders for plant improvement. Transgenic approaches in food plants have raised concerns on the merits, social implications, ecological risks and true benefits of plant biotechnology. The recently acquired ability to precisely edit plant genomes by modifying native genes without introducing new genetic material offers new opportunities to rapidly exploit natural variation, create new variation and incorporate changes with the goal to generate more productive and nutritious plants.